2012
DOI: 10.1007/s00264-012-1704-5
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT tracer uptake is influenced by tunnel orientation and position of the femoral and tibial ACL graft insertion site

Abstract: Purpose SPECT/CT is a hybrid imaging modality, which combines a 3D scintigraphy (SPECT) and a conventional computerised tomography (CT). SPECT/CT allows accurate anatomical localisation of metabolic tracer activity. It allows the correlation of surgical factors such as tunnel position and orientation with mechanical alignment, clinical outcome and biological factors. The purpose of this study was to investigate whether the SPECT/CT tracer uptake (intensity and distribution) correlates with the stability and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“…In a series of carefully conducted studies, Hirschmann et al and Rasch et al [63,64] established that intensity of tracer uptake as visualized by SPECT/CT reflects the specific loading patterns of the knee with regard to its alignment and that abnormal increases in tracer uptake are reversible on tibial osteotomy correcting for varus misalignment [65,66]. Furthermore, they proposed a standardized, semiautomatic approach for the evaluation of tracer uptake in the knee in relation to component position following arthroplasty [67]. Using this method, they demonstrated that SPECT/CT imaging had therapeutic impact in 19/23 of Fig.…”
Section: Differential Diagnosis Of Pain Associated With the Musculoskmentioning
confidence: 99%
“…In a series of carefully conducted studies, Hirschmann et al and Rasch et al [63,64] established that intensity of tracer uptake as visualized by SPECT/CT reflects the specific loading patterns of the knee with regard to its alignment and that abnormal increases in tracer uptake are reversible on tibial osteotomy correcting for varus misalignment [65,66]. Furthermore, they proposed a standardized, semiautomatic approach for the evaluation of tracer uptake in the knee in relation to component position following arthroplasty [67]. Using this method, they demonstrated that SPECT/CT imaging had therapeutic impact in 19/23 of Fig.…”
Section: Differential Diagnosis Of Pain Associated With the Musculoskmentioning
confidence: 99%
“…On the coronal 99m Tc-DPD SPECT image (d), increased tracer uptake (arrow) is seen in the medial femoral condyle corresponding to the well-fixed osteochondral fragment on the CT image (c, arrow) and the SPECT/ CT image (e, arrow). The articular cartilage surface is nicely visible and well preserved on SPECT/CT arthrography group for the evaluation of anterior cruciate ligament grafts, trying to correlate the location of increased uptake with biomechanical appreciation and clinical symptoms [40,41]. A novel four-dimensional SPECT/CT approach correlates tracer uptake and joint replacement component positioning in patients after total knee arthroplasty, showing excellent inter-and intraobserver reliabilities, and might therefore be the evaluation standard of the future [42,43].…”
Section: Kneementioning
confidence: 99%
“…It has been suggested that the intensity of uptake in SPECT/CT was associated with loading of the knee and with osteoarthritis [7]. Another paper suggested that SPECT/CT uptake patterns might help to predict graft failure after anterior cruciate ligament reconstruction [8]. In addition, it has been reported that in patients with postoperative knee pain, SPECT/CT could provide beneficial information in establishing a follow-up plan [9].…”
Section: Introductionmentioning
confidence: 97%